1996
DOI: 10.1162/neco.1996.8.7.1521
|View full text |Cite
|
Sign up to set email alerts
|

Learning and Generalization in Cascade Network Architectures

Abstract: Incrementally constructed cascade architectures are a promising alternative to networks of predefined size. This paper compares the direct cascade architecture (DCA) proposed in Littmann and Ritter (1992) to the cascade-correlation approach of Fahlman and Lebiere (1990) and to related approaches and discusses the properties on the basis of various benchmark results. One important virtue of DCA is that it allows the cascading of entire subnetworks, even if these admit no error-backpropagation. Exploiting this f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Previous research did not find out the conclusive decision about generalization capabilities of standard CCN and flat CCN. Littman and Ritter suggested that standard CCN generalized better than the flat CCN whereas Sjogaard suggested that the flat CCN was a better choice than the standard CCN [39,10]. Prechelt empirically found that the flat variant was superior to the cascade variant for some problems [17].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research did not find out the conclusive decision about generalization capabilities of standard CCN and flat CCN. Littman and Ritter suggested that standard CCN generalized better than the flat CCN whereas Sjogaard suggested that the flat CCN was a better choice than the standard CCN [39,10]. Prechelt empirically found that the flat variant was superior to the cascade variant for some problems [17].…”
Section: Discussionmentioning
confidence: 99%
“…Our indirect-mapping EKM resembles the EKM models of (Littmann and Ritter, 1996;Walter and Schulten, 1993), which utilize locally linear mappings. In their models, each neuron stores both the motor control vector and the matrix of motor control parameters as output weights (Eq.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, we have shown that training the control parameters with recursive least squares enables faster convergence and better performance compared to gradient descent. Their EKM models (Littmann and Ritter, 1996;Walter and Schulten, 1993) have only used gradient descent to learn the control parameters.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Ash, 1989, Wang et al, 1994, propose addition of units in the hidden layers of standard MLPs during normal backpropagation training, but this approach severely disturbs the training process because of the interaction of hidden units. Not even constructive unit splitting with reasonable initializations for the new units works well Hanson, 1989, WynneJones, 1991. Littmann and Ritter, 1993 propose direct cascading where local linear maps or di erent neural modules are cascaded and produce the output from the union of the original network inputs and the outputs of previous modules.…”
Section: Related Workmentioning
confidence: 99%